Deterministic model of biomolecular networks with stimuli-responsive properties. (May 2015) - Creasy, M Austin; Freeman, Eric C; Philen, Michael K; Leo, Donald J
A deterministic model is presented for predicting the passive and stimuli-responsive characteristics of biomolecular networks. These biomolecular networks consist of multiple bilayer interfaces that can incorporate stimuli-responsive molecules such as peptides and proteins. A model is presented and a lumped parameter method is used to obtain the network equations for several case studies. The model is then utilized to predict the response of a biomolecular network that exhibits rectification behavior due to the presence of voltage-responsive protein incorporated into the interfacial bilayer. This article demonstrates the electric response of systems of biomolecular networks and prompts further research into their use for engineering applications.